School leadership and organization in times of complexity: paths to a collaborative and regenerative school - Generosa Pinheiro; José Matias Alves; Lídia Serra (Frontiers in Education)
This article describes a possible metamorphosis of school grammar—the underlying structures, practices, and norms that shape how schools function—through the organization of teaching by educational teams. Educational teams can serve as catalysts for transforming schools into more personalized, flexible, interactive, and adaptive systems. It also discusses the implications of these structural changes for the shift toward more integrative leadership models, such as collaborative and regenerative leadership. Hence, the article tries to fill a conceptual gap concerning how educational teams can serve as a structural level for reconfiguring the traditional grammar of schooling through an integrative lens that implies school actors. To present further implications for practice, this article, a conceptual analysis, examines the role of principals, middle leaders, and teacher leaders in building these leadership perspectives. This whole approach emphasizes the importance of a joint, articulated and holistic effort, which will require a change of vision and purpose, but also of structures, of leadership and of the school cultures, in an ecological dynamic, to achieve the sustainable success of the school and the attainment of the goals of quality, equity, diversity and social justice.